FIRST RECORDS OF ROTIFERS PROALES GIGANTEA (GLASCOTT, 1893) (PROALIDAE) AND ASCOMORPHA SALTANS INDICA WULFERT, 1966 (GASTROPODIDAE) IN FRESHWATERS OF TURKEY - Bulut, Hilal (Parlar Research & Technology Ug, 2020)
In the course of examination of the zooplankton of Han Stream (Malatya, Turkey) between September 2012 and August 2013, 20 zooplankton species group taxa were identified. These were 13 species and 1 subspecies of the Rotifera, four species of the Cladocera and two species of the Copepoda. Among rotifers, there are two new geographical records for Turkey: Proales gigantea (Glascott, 1893), a species parasitizing eggs of aquatic snails, and Ascomorpha saltans indica Wulfert, 1966. Among all zooplankton was represented with Rotifera 70%, Cladocera 20% and Copepoda 10%. This new records that discovered are monogonont rotifer. Photo of the new recorded species were illustrated using light microscopy. Scanning electron microscope image was taken for trophi of Ascomorpha saltans indica.
Keywords: Parasitic rotifer; Monogononta; Turkey